A new species of Chaetolonchaea Czerny (Diptera: Lonchaeidae) from China, a larval pest on chives - Zhang, Ting-Ting; Liu, Fang; Macgowan, Iain; Xue, Ming (Zootaxa, 2017)
A new species, Chaetolonchaea alliumi sp. nov. is described and illustrated. The larvae of this species are found in the bulbs of chives (Allium tuberosum Rottl. ex Spreng.), and the species is an important pest of liliaceous vegetables. A key to the eight known species of world Chaetolonchaea Czerny, 1934 is included. The egg, larva and larval skeleton of genus Chaetolonchae are illustrate for the first time. Photographs of the puparium, host plant and injury symptoms are also provided.